(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Globally, each year nearly 400,000 children and adolescents, who is at the age of 0 to19 years, old develop cancer. Most common type of cancer found among the children is leukaemia’s, brain cancers, lymphomas and solid tumours, such as neuroblastoma and Wilms tumour’s. The objective of study: assess the grade of the oral mucositis among children with cancer receiving chemotherapy, evaluate effect of glycerin application on oral mucositis among experimental group I, to evaluate effect of chlorhexidine on oral mucositis among experimental group II, To compare the effect of glycerine application and chlorhexidine on oral mucositis, To find association of oral mucositis with selected demographic variables. Material and Methods: In present study, researcher adopted Quantitative Approach with True experimental design. It was carried out on 60 samples Effectiveness of glycerine application versus chlorhexidine mouth wash on oral mucositis among children with cancer receiving chemotherapy. Data analysis was done using descriptive statistics and inferential statistics. Result Major findings of the study stated that, Experimental Group I on day1 first observation, 57% of the children with cancer receiving chemotherapy had Grade I oral mucositis, 40% of them had Grade II oral mucositis and 3.3% of them had Grade III oral mucositis.In Experimental Group II on day1 of first observation, 47% of the children with cancer receiving chemotherapy had Grade I oral mucositis, 33% of them had Grade II oral mucositis and 20% of them had Grade III oral mucositis. That is shows that information booklet was effective method to increase knowledge. Conclusion The study concluded that this study is saying that both the glycerin and chlorhexidine treatment is effective for the treatment of chemotherapy-induced oral mucositis for all grades.